INCLUSIVE LEARNING STRATEGY BASED ON COLLABORATION TO IMPROVE GROSS MOTOR SKILLS OF EARLY CHILDHOOD - Wijaya Pipit Rika; Budiyanto Budiyanto; Sartinah Endang Pudjiastuti (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The purpose of this study is to identify and implement effective collaboration-based inclusive learning strategies in improving gross motor skills in early childhood, and to evaluate their impact on children's physical development. The problems of this study include several important aspects, namely: limited implementation of inclusive learning strategies in PAUD institutions, lack of collaboration between teachers, parents, and professionals in developing children's gross motor skills, and minimal variation in learning activities that reduce children's physical activity which has an impact on gross motor development. This study uses a quantitative quasi-experimental. Pretest-posttest research design with (one-group pretest-posttest design). Research Object 20 students, Collaboration-based inclusive learning strategies have been proven effective in improving gross motor development in early childhood through a comprehensive approach. This strategy not only helps children's physical development, but also encourages their social-emotional development through positive interactions with peers, as well as building self-confidence and cooperation skills that are important for their overall development